Combined cultivation and single-cell approaches to the phylogenomics of nucleariid amoebae, close relatives of fungi. (7th October 2019) - Galindo, Luis Javier; Torruella, Guifré; Moreira, David; Eglit, Yana; Simpson, Alastair G. B.; Völcker, Eckhard; Clauß, Steffen; López-García, Purificación
Abstract : Nucleariid amoebae (Opisthokonta) have been known since the nineteenth century but their diversity and evolutionary history remain poorly understood. To overcome this limitation, we have obtained genomic and transcriptomic data from three Nuclearia, two Pompholyxophrys and one Lithocolla species using traditional culturing and single-cell genome (SCG) and single-cell transcriptome amplification methods. The phylogeny of the complete 18S rRNA sequences of Pompholyxophrys and Lithocolla confirmed their suggested evolutionary relatedness to nucleariid amoebae, although with moderate support for internal splits. SCG amplification techniques also led to the identification of probable bacterial endosymbionts belonging to Chlamydiales and Rickettsiales in Pompholyxophrys . To improve the phylogenetic framework of nucleariids, we carried out phylogenomic analyses based on two datasets of, respectively, 264 conserved proteins and 74 single-copy protein domains. We obtained full support for the monophyly of the nucleariid amoebae, which comprise two major clades: (i) Parvularia–Fonticula and (ii) Nuclearia with the scaled genera Pompholyxophrys and Lithocolla . Based on these findings, the evolution of some traits of the earliest-diverging lineage of Holomycota can be inferred. Our results suggest that the last common ancestor of nucleariids was a freshwater, bacterivorous, non-flagellated filose and mucilaginous amoeba. From the ancestor, two groups evolved to reach smaller ( Parvularia–Fonticula ) and larger ( Nuclearia and related scaled genera) cell sizes, leading to different ecological specialization. The Lithocolla + Pompholyxophrys clade developed exogenous or endogenous cell coverings from a Nuclearia -like ancestor. This article is part of a discussion meeting issue 'Single cell ecology'.